2007
DOI: 10.1038/nmeth1041
|View full text |Cite
|
Sign up to set email alerts
|

Generation of functional hemangioblasts from human embryonic stem cells

Abstract: Recent evidence suggests the existence of progenitor cells in adult tissues that are capable of differentiating into vascular structures as well as into all hematopoietic cell lineages. Here we describe an efficient and reproducible method for generating large numbers of these bipotential progenitors-known as hemangioblasts-from human embryonic stem (hES) cells using an in vitro differentiation system. Blast cells expressed gene signatures characteristic of hemangioblasts, and could be expanded, cryopreserved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
193
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 182 publications
(203 citation statements)
references
References 32 publications
(51 reference statements)
7
193
0
3
Order By: Relevance
“…Therefore, the hemogenic endothelial cells have characteristics of definitive hemangioblasts in late somite stage embryos (Jaffredo et al, 2005;Tavian and Peault, 2005). These early observations in chick, mouse, and human embryos play an important role in the evolution of the hemangioblast concept and the ultimate identification of hemangioblasts in mouse and human ESC-derived embryoid bodies (EBs), and mouse and zebrafish embryos as described below (Choi et al, 1998;Lu et al, 2006;Vogeli et al, 2006;Kennedy et al, 2007).…”
Section: The Hemangioblast Hypothesis Was Proposed and Supported Frommentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, the hemogenic endothelial cells have characteristics of definitive hemangioblasts in late somite stage embryos (Jaffredo et al, 2005;Tavian and Peault, 2005). These early observations in chick, mouse, and human embryos play an important role in the evolution of the hemangioblast concept and the ultimate identification of hemangioblasts in mouse and human ESC-derived embryoid bodies (EBs), and mouse and zebrafish embryos as described below (Choi et al, 1998;Lu et al, 2006;Vogeli et al, 2006;Kennedy et al, 2007).…”
Section: The Hemangioblast Hypothesis Was Proposed and Supported Frommentioning
confidence: 99%
“…Most recently, Keller's group has isolated and characterized human BL-CFCs that have almost identical molecular signatures and potential to clonally generate endothelial and hematopoietic lineages as those in mouse BL-CFCs . Independently, Lu and colleagues have also isolated similar human BL-CFCs, and in addition, they have shown that transplanted blast cells could contribute to neo-vascular regeneration in damaged vessels using several animal models (Lu et al, 2006). Because the culture conditions each laboratory used are quite different, the above hemangioblast-like cell populations may not represent the same cells.…”
Section: Hemangioblast or Bl-cfc Is Found In Ebsmentioning
confidence: 99%
See 2 more Smart Citations
“…H ematopoiesis in the early mouse embryo has been recapitulated by in vitro differentiation culture of human and murine embryonic stem cells (mESCs) by which mesodermal cells commit to the hematopoietic lineage before giving rise to other blood cells [1][2][3][4][5][6][7]. During embryogenesis, hematopoietic cells originate from the lateral plate mesoderm in an ordered program of development occurring in conjunction with cells of the cardiovascular system and share a common precursor, the hemangioblast [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%